2012
DOI: 10.1093/nar/gks1265
|View full text |Cite
|
Sign up to set email alerts
|

Dfam: a database of repetitive DNA based on profile hidden Markov models

Abstract: We present a database of repetitive DNA elements, called Dfam (http://dfam.janelia.org). Many genomes contain a large fraction of repetitive DNA, much of which is made up of remnants of transposable elements (TEs). Accurate annotation of TEs enables research into their biology and can shed light on the evolutionary processes that shape genomes. Identification and masking of TEs can also greatly simplify many downstream genome annotation and sequence analysis tasks. The commonly used TE annotation tools RepeatM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
233
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(248 citation statements)
references
References 12 publications
1
233
0
Order By: Relevance
“…REP522, originally called a telomeric satellite, is a largely palindromic, unclassified interspersed repeat of $1.8 Kb in size (28). We observed that out of 72 promoters overlapping REP522, 25 were upregulated in cancer (odds ratio, 62.05).…”
Section: Bidirectional Transcription From Rep522 Satellite Repeat Is mentioning
confidence: 87%
“…REP522, originally called a telomeric satellite, is a largely palindromic, unclassified interspersed repeat of $1.8 Kb in size (28). We observed that out of 72 promoters overlapping REP522, 25 were upregulated in cancer (odds ratio, 62.05).…”
Section: Bidirectional Transcription From Rep522 Satellite Repeat Is mentioning
confidence: 87%
“…To determine the signaling domains in the DosM sequence, we identified the limits of the MCPsignal (PF00015) Pfam (41) protein domain model with HMMER3 (42). To determine the heptad class of each domain, we used hidden Markov models provided previously (28,43).…”
Section: Methodsmentioning
confidence: 99%
“…To be specific, 2.8 % of DNA transposons, 8.3 % of LTR retrotransposons, and 33.7 % of non-LTR retrotransposons (16.9 % of LINE, 10.6 % of Alu, 0.2 % of SVA, 6 % of others) exist in human genome (Cordaux and Batzer 2009). Recently, computer program RepeatMasker has been updated, and it has provided classification of TEs in most of the living things (Carbone et al 2014;Jurka et al 2005;Smit et al 2010;Walker et al 2012;Wheeler et al 2012). Table 1 is supporting the information of TEs distribution in human and diverse primates.…”
Section: Transposable Element Distribution Of Human and Various Primatesmentioning
confidence: 99%